2005
DOI: 10.1007/s10194-005-0208-8
|View full text |Cite
|
Sign up to set email alerts
|

Post–traumatic headache from moderate head injury

Abstract: The onset of post-traumatic headache occurs frequently in children, where it is often caused by severe head injuries, therefore, it is part of a post-traumatic syndrome, rather than of an independent headache and in this case no cause is clearly evident. The problem, conversely, arises in post-traumatic headache after a light trauma, since it is difficult to establish the cause-effect link. We have studied PTH incidence for one year in the patients of the emergency ward of the Saint Charles of Nancy Hospital, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
2
6
2
Order By: Relevance
“…[4][5][6][7][8][9]15,16 However, migraine-like headache was the most common type in our study as opposed to the study of D'Onofrio et al 17 in adults in which most of the patients had chronic persistent tension headache. This difference may be related to differences in the development and distribution of pain receptors and in pain perception between the developing and the mature brain.…”
Section: Discussioncontrasting
confidence: 79%
“…[4][5][6][7][8][9]15,16 However, migraine-like headache was the most common type in our study as opposed to the study of D'Onofrio et al 17 in adults in which most of the patients had chronic persistent tension headache. This difference may be related to differences in the development and distribution of pain receptors and in pain perception between the developing and the mature brain.…”
Section: Discussioncontrasting
confidence: 79%
“…The prevalence of CPTH in this Scottish population (6.8%, 95% CI 3.0-13.0) is in keeping with the low prevalence (3.2%) noted in a recent large Italian multicentre study of 1656 children. 6 It is very likely that the reasons for the low prevalence rates in the two studies is related to the use of similar methodology, use of the IHS classification of headache and HI, and the application of strict criteria for the definition of CPTH. The strength of our single-centre study is the high quality prospective data on headache that are consistent, reproducible, and reliable.…”
Section: Discussionmentioning
confidence: 99%
“…CPTH followed a benign course with complete resolution of headache in the majority of children within 6 months. 6 The pathophysiology of CPTH is not well understood. Anatomical and physiological changes include degeneration of nerve fibres, reduced regional cerebral blood flow, and diffuse axonal injury at the grey-white matter interface.…”
mentioning
confidence: 99%
“…Recent rigorous studies in the pediatric head injury population found prevalence rates of chronic PTH to be 3.2% and 6.8% 98,99 . Kirk recently 98 found that the majority of chronic PTH resolved by 1 year.…”
Section: Risk Factors For Pth and Prognosismentioning
confidence: 99%